LINGUOCULTURAL AND STRUCTURAL-SEMANTIC FEATURES OF UZBEK AND ENGLISH TOPONYMS: A COMPARATIVE ANALYSIS OF TERMEZ AND WINCHESTER PLACE NAMES (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article presents a comparative linguocultural study of Uzbek and English toponyms based on the examples of Termez (Uzbekistan) and Winchester (England). The research focuses on the structural-semantic characteristics, etymological origins and cultural symbolism of oikonyms and urban toponymic objects such as streets, districts, public places, and facilities. The study applies descriptive, etymological, componential and comparative methods to identify similarities and differences between the toponymic systems.